The Baxters : a prequel - Kingsbury, Karen (New York : Atria Books, 2022)
On Kari Baxter's wedding day, a building storm brings conflict and doubt to the family until a moment of danger reveals important truths, which could bring them back together or tear them apart
A terrible storm builds in the morning sky over Bloomington, Indiana, as Elizabeth Baxter prepares to celebrate her daughter Kari's wedding to Tim Jacobs. Elizabeth can't shake a growing sense that something bad is about to happen. In the midst of the family, Kari Baxter is starting to panic. Is marrying Tim a mistake? Her brother Luke is angry and resentful of their sister Ashley, who has recently returned from Paris, a single mom with a son she too often leaves with their parents. At the same time, Ashley and their sister Brooke have lost the faith that is the family's glue. Against all this, Kari sees Ashley rejecting her longtime love, Landon Blake, who clearly cares for her, no matter what happened in Paris. When the storm reaches a terrifying crescendo, a shocking moment of danger brings important truths to light. At the end of the long day, can the Baxters remain a family, tested but stronger? -- adapted from jacket
"Soon to be a TV series"--Dust jacket
"A Baxter Family Stand-Alone title."
Includes discussion questions (pages 317-319)
Keywords: Weddings -- Fiction; Storms -- Fiction; Families -- Fiction; Brothers and sisters -- Fiction; Christian life -- Fiction; Bloomington (Ind.) -- Fiction; Fictional Work; Christian fiction; Romance fiction; Religious fiction; Domestic fiction; Novels